Influence of waterlogging stress on nutrient uptake and biochemical parameters in rice (Bangladesh Journal of Botany, 2026)
This study aimed to investigate the effect of waterlogging on nutrient uptake and its association with biochemical parameters, including reducing and total sugars, proline content, and antioxidant enzyme activities in Oryza sativa L. grown under hydroponic culture. Following up to 21 days of waterlogging induced by a continuous nitrogen gas supply, K+ accumulation significantly decreased by up to 35.6% in roots and 40% in shoots, while Na+ accumulation notably increased by 64% in roots and 58% in shoots at 21 days after treatment, which reflects an imbalance in K+/Na+  homeostatis. NO3⁻ content in roots and shoots decreased up to 23 and 27.8%, respectively. Furthermore, Ca2+ and Mg2+ levels in roots decreased by 9.7 and 25%, respectively. On the other hand, Fe2+ accumulation increased by 30% in roots after 21 days of exposure to waterlogging. Waterlogging stress triggered a notable rise in reducing sugar (55.5%), total sugar (37.6%), and proline (92.2%) content particularly in roots, reflecting a clear metabolic response to prolonged hypoxia. Furthermore, a 3.3-fold increase in superoxide dismutase 2.1-fold rise in peroxidase and a 2.7-fold increase in catalase activity in leaves indicated an activation of primary enzymatic antioxidant responses. Although these nutrient and biochemical changes are immediate responses to hypoxia, they are ultimately insufficient to prevent declines in overall growth. Comprehending these primary physiological and biochemical alterations provides essential baseline insights for developing waterlogging tolerant rice cultivars.Bangladesh J. Bot. 55(2): 355-362, 2026 (June)